Spatial distribution of selected trace metals at tropical riverine system - Ng, Li Qing; Mohamed, Khairul Nizam; Lasumin, Nazerita (Oriental Scientific Publishing Company, 2022)
This study determined the distribution of selected trace metals (Cu, Cd, Zn and Pb) in the dissolved and particulate samples at Sungai Buloh river, Malaysia. The dissolved Zn, Cd, Cu and Pb concentration along the river was in the safety range. The dissolved and particulate Zn, Pb, Cu and Cd concentration was measured and recorded. We found that most of the metals exist in the particulate form and a consistent distribution coefficient (KD) value indicated a low metals deposition occurred along the river. Therefore, it could suggest that most of the anthropogenic input in the upper stream was transported along the river and it might deposited at the estuarine of the river, which could affect the safety level of these metals at the surface sediment and in the aquatic organisms in the study area.